IDDF2020-ABS-0205 The impact of the COVID-19 pandemic on irritable bowel syndrome. (18th November 2020) - Zi Quek, Sabrina Xin; Ling Loo, Evelyn Xiu; Demutska, Alla Demutska; Chua, Chun En; Kew, Guan Sen; Wong, Scott; Lau, Hui Xing; Sarah Low, En Xian; Loh, Tze Liang; Ooi, Shien Lung; Hung, Emily CW; Masudur Rahma, M; et al.
Abstract : Background: Gastrointestinal manifestations of the COVID-19 pandemic may mimic Irritable Bowel Syndrome (IBS), and social distancing measures may affect IBS patients negatively. We aimed to study the impact of COVID-19 on respondents with IBS. Methods: We conducted an anonymised survey using MySurvey platform from May to June 2020 in 35 countries. The general public's knowledge, attitudes and practices regarding personal hygiene and social distancing during this COVID-19 pandemic and the psychological impact of COVID-19 were assessed. Statistical analysis was performed to determine the differences in well-being and compliance to social distancing measures between IBS and non-IBS respondents. Factors associated with worsening of IBS symptoms were evaluated. For newly developed IBS-like symptoms, subjects must fulfill ROME IV criteria. Results: Out of 2704 respondents, 2024 (74.9%) did not have IBS, 305 (11.3%) had IBS and 374 (13.8%) did not know what IBS was. Respondents with IBS reported significantly worse emotional, social and psychological well-being compared to non-IBS respondents and were less compliant to social distancing (28.2% vs 35.3%, p =0.029, table 1 ). Of the non-IBS respondents, 96 (4.7%) developed new IBS-like symptoms. Among IBS respondents, the majority reported no change in symptom severity (61.6%), while 26.6% reported improvement and 11.8% reported worsening in IBS symptoms. A higher proportion of respondents with no change in the severity of IBS symptoms was willing to practice social distancing indefinitely compared to those who deteriorated (74.9% vs 51.4%, p =0.016, table 2). In multivariate analysis (table 3), willingness to continue social distancing for only another 2–3 weeks was significantly associated with higher odds of worsening IBS while better emotional well-being was associated with lower odds. Flourishing was excluded from analysis due to overlap with emotional well-being. *Excluded from multivariable analysis due to 0 respondents in reference categories for respondents with no change in control IBS Conclusions: Our study showed differences in well-being and compliance to social distancing between IBS and non-IBS respondents, and these factors influence the worsening in severity of IBS. Further research will focus on how occupational stress and dietary changes may influence IBS symptoms